Exposure and physical vulnerability indicators to assess seismic risk in urban areas: a step towards a multi-hazard risk analysis - Xofi, Maria (2022)
Understanding the impacts of multi-hazard risk in urban areas is a fundamental step towards the adoption of resilience-enhancement and disaster prevention strategies, underpinning institutional adjustments aimed at improving the capacity of the authorities and stakeholders to manage risk. Within this framework, the work presented in this paper seeks to identify and analyze a set of exposure and buildings’ physical vulnerability indicators to be used as input to a parametric-based seismic vulnerability assessment methodology for the unreinforced masonry (URM) building stock of Lisbon Metropolitan Area (LMA). For this approach, data from the 2011 Census survey are used to define the parameters describing the building’s physical vulnerability and characterise the level of exposure in the study area. These results are then combined with the hazard component into a GIS tool. Seismic vulnerability results are presented for the URM building stock in LMA, and a more detailed analysis is conducted for the building stock of Set ubal municipality. Finally, risk outputs are presented and briefly discussed. Ultimately, understanding the impact and extent of multi-hazards can help prioritize resilienceincreasing actions and disaster prevention measures to mitigate and manage natural hazards.